Impact of Covid-19 on Physics Learning in High School Students - Ratu Winda Septiawati (FKIP UM Pontianak, 2021)
During the Covid-19 Pandemic, the Education System in Indonesia also experienced a change, namely by replacing face-to-face learning activities directly at schools or colleges with online learning activities from their respective homes. This online learning certainly has an impact on high school student interest and learning motivation. Some students think that physics is one of the subjects that are complicated, and boring. The bad opinion of these students certainly reduces students' interest in studying physics. What's more, currently Indonesia is implementing an online learning system. Therefore, there needs to be a proper teaching strategy carried out by teachers, especially in physics subjects. The appropriate teaching strategy is in order to increase students' interest in learning in physics, and to change the perception of some students who think physics is complicated and boring. Because regardless of the situation, it is important to study physics because physics is the study of all the events that occur in the universe. Writing this paper aims to find out what are the impacts of online learning during the Covid-19 pandemic on learning interest and motivation in high school students and to be able to find out the right teaching strategies in physics lessons online. The method used in this study is the literature method (literature review) from several reading sources.